Treatment of early breast cancer patients: evidence, controversies, consensus: focusing on systemic therapy. German experts’ opinions for the 16th International St. Gallen Consensus Conference (Vienna 2019) - Lüftner, Diana; Bauerfeind, Ingo; Schneeweiss, Andreas (Breast care, 2019)
A German working group of leading breast cancer experts have discussed the votes at the International St. Gallen Consensus Conference in Vienna for the treatment of primary breast cancer with regard to the German AGO (Arbeitsgemeinschaft Gynäkologische Onkologie) recommendations for clinical practice in Germany. Three of the German breast cancer experts were also members of this year’s St. Gallen panel. Comparing the St. Gallen recommendations with the annually updated treatment recommendations of the Gynecological Oncology Working Group (AGO Mamma 2019) and the German S3 Guideline is useful, because the recommendations of the St. Gallen panel are based on expert opinions of different countries and disciplines. The focus of this article is on systemic therapy. The motto of this year’s 16th St. Gallen Consensus Conference was “Estimating the magnitude of clinical benefit.” The rationale behind this motto is that, for every treatment decision, a benefit-risk assessment must be taken into consideration for each patient.
Gesehen am 14.01.2020